Motions Analysis Investigation of a 12 Meter Catamaran Tourism Boat on Passenger Comfort Criteria Case Study "MV Garuda Ngelayang" - Yeddid Yonatan Eka Darma; Hery Inprasetyobudi; Rochmad Eko Prasetyaning Utomo; Galih Hendra Wibowo; Ahmad Hidayat; Albert Daniel Saragih (International Journal of Marine Engineering Innovation and Research, 2023)
Bangsring Beach is one of the leading tourist destinations in Banyuwangi Regency. Bangsring Beach which focuses on underwater tourism (Bangsring Underwater) is a coral reef-based tourism that can only be accessed by diving and snorkeling. But only in that way to enjoy Bangsring Underwater tourism, the construction of a 12 m catamaran with a bottom glass is carried out so that tourists who cannot dive and snorkel can enjoy the beauty of Bangsring Underwater. To ensure the comfort and safety of passengers, a simulation analysis of the movement of the existing 12-merter catamaran is carried out. This simulation was carried out with the general design of a catamaran modeled 1:1 with a LOA of 12 m, B 5.6 m, H 1.85 m, and Vs 10 knots. On the 1:1 ship, an exsisting process is carried out at each ship station to get a line plan for the Garufa Ngelayang ship then 3D modeling is carried out based on the reference from the line plan drawing. Ship motion simulations are carried out to determine the ship's response when hit by waves from various directions which are presented in the RAO (Response Amplitude Operator) graph using the CFD method which is based on a 3D model. Simulations were carried out with a wave height of 1.25 m in Bangsring waters with a fully loaded ship with a wave direction of 0o following sea; Stern Quarter 45o, 315o; Beam Sea 90o, 315o; Bow Quarter 135o, 225o; and Head Sea 180o. With a comfortable ship condition with 2.052 s of ship shaky period.